Fractional carbon dioxide (CO₂) laser alone versus fractional CO₂ laser combined with triamcinolone acetonide or tricholoroacetic acid in keloid treatment: A comparative clinical & radiological study - Elazhary, Engy; Abd Al-Salam, Fatma; Abd El-Hafiz, Hala; Maghraby, Hala (Dermatology Practical & Conceptual, 2022)
Introduction: Keloids are benign fibro-proliferative scarring extending outside the initial wound. Different modalities of treatment as intralesional corticosteroid injection, fractional CO₂ laser and others can be used either as mono or combined therapies.Objectives: To assess the role of fractional CO2 laser versus fractional CO2 laser accompanied with either triamcinolone acetonide or trichloroacetic acid 20% in keloid treatment clinically and radiologically.Methods: The current study was conducted on 45 Egyptian participants with keloid scar at different sites of the body. They were classified into three groups treated by fractional CO2 laser only (group I), fractional CO2 laser followed by triamcinolone acetonide (group II) or trichloroacetic acid application (group III) respectively. Evaluation of the keloid was done with Vancouver Scar Scale (VSS) and Color Doppler Ultrasound (CDU) before and after treatment. Four sessions, one month apart were applied for the patients. They were followed up for 8 weeks after the last session.Results: After treatment, there was high statistically significant reduction in Vancouver Scar Scale among the three groups (P value ≤ 0.001), reduction was more in group II then I then III. Also, high statistically significant reduction in keloid scar thickness assessed by Doppler was recorded (P value ≤0.001 in group II and P value ≤0.01 in group I & III).Conclusions: Combined therapy is favorable in treatment of keloids. Trichloroacetic acid is a promising modality in treating keloid; hence it can be tried in different combinations. Color Doppler Ultrasound is a promising method of keloids pre- and post-treatment assessment.